2015
DOI: 10.1371/journal.pone.0118270
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Molecular Approach for Chromosomal Phasing

Abstract: Determining the chromosomal phase of pairs of sequence variants – the arrangement of specific alleles as haplotypes – is a routine challenge in molecular genetics. Here we describe Drop-Phase, a molecular method for quickly ascertaining the phase of pairs of DNA sequence variants (separated by 1-200 kb) without cloning or manual single-molecule dilution. In each Drop-Phase reaction, genomic DNA segments are isolated in tens of thousands of nanoliter-sized droplets together with allele-specific fluorescence pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 38 publications
0
77
0
1
Order By: Relevance
“…Recently, it was shown that this technique could also be used to phase variants separated by up to 200 Kb (Regan et al 2015), which has already been applied to fusion transcript detection (Hoff et al 2016) or to phase deletions into haplotypes (Boettger et al 2016). Here, we have developed new ddPCR assays to genotype quickly and reliably human polymorphic inversions flanked by large IRs, and thanks to the genotype data we demonstrate that most of these inversions are recurrent and that inversion alleles are associated to gene expression changes.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, it was shown that this technique could also be used to phase variants separated by up to 200 Kb (Regan et al 2015), which has already been applied to fusion transcript detection (Hoff et al 2016) or to phase deletions into haplotypes (Boettger et al 2016). Here, we have developed new ddPCR assays to genotype quickly and reliably human polymorphic inversions flanked by large IRs, and thanks to the genotype data we demonstrate that most of these inversions are recurrent and that inversion alleles are associated to gene expression changes.…”
Section: Introductionmentioning
confidence: 92%
“…AFR, Africans; EAS, East-Asians; EUR, Europeans. ddPCR technology allows us to quantify how close two independent sequences are within a DNA molecule based on their simultaneous amplification in a higher number of droplet partitions than expected by chance (Regan et al 2015). Thus, for each inversion we designed three amplicons in the unique sequence outside the IRs (A or D) and at both ends of the inverted segment (B and C) ( Fig.…”
Section: Table 1 Inversion Features and Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of two different targets in cis and nearby, there will be an excess of double positive partitions. We can measure the concentration of each target using standard approaches but may miss the fact the targets are indeed linked [48]. Current standard analysis tools can report the concentration of the linked molecules using linkage-based assays to measure cis versus trans configuration of targets and potential structural rearrangements [49].…”
Section: Considerations For Accurate Quantificationmentioning
confidence: 99%
“…Reactions contained 20 ng of genomic DNA from Patient 2, a 5′ fluorescein (FAM)‐labeled locked nucleic acid (LNA) probe targeting the c.460G > C variant, a hexachlorofluorescein (HEX)‐labeled LNA probe targeting the c.1129G > C variant, 2 primer sets to amplify the respective target regions, and ddPCR Supermix for Probes (no dUTP; Bio‐Rad Laboratories). We phased 2 variants as previously described …”
Section: Methodsmentioning
confidence: 99%